Sequential mediation of early temperament and eating behaviors in the pathways from feeding practices to childhood overweight and obesity - Zhang, Xiaoning; Zhou, Qiong; Vivor, Nathaniel Kossi; Liu, Wei; Cao, Junli; Wang, Sheng (Frontiers in Public Health, 2023)
Introduction Childhood eating behaviors and temperament may have important implication for constructing the pathways from maternal feeding practices to childhood overweight and obesity (OW/OB). Examining multiple feeding styles simultaneously to childhood OW/OB is critical through the mediators of early childhood temperament and eating behaviors. Methods This cross-sectional study recruited mothers mainly responsible for child care from two hospitals and two healthcare centers in eastern China. Sociodemographic characteristics, and data from the Infant Feeding Style Questionnaire (IFSQ), the short form of Children Behavior Questionnaire [Revised (IBQ-RSF)], and the Child Eating Behavior Questionnaire for toddler (CEBQ-T) were collected. Weight and recumbent length were measured to calculate the age- and sex-specific body mass index (BMI) z-scores (BMIz). The structural equation modeling (SEM) approach was used to examine direct and indirect pathways from five maternal feeding styles to childhood OW/OB through temperament and eating behaviors. Results A total of 486 children were recruited, 73 (15.02%) children were OW/OB; the age of the children was 14.55 (SD = 5.14) months, and the age of the mothers was 29.90 (SD = 3.63) years. The responsive feeding exerted significant direct (β = −0.098), indirect (β = −0.136) and total (β = −0.234) effects on childhood OW/OB. Restrictive feeding had significant direct (β = 0.222), indirect (β = 0.102) and total (β = 0.324) effects on childhood OW/OB. Indulgent feeding had significant direct (β = 0.220), indirect (β = 0.063), and total (β = 0.283) effects on childhood OW/OB. Pressuring feeding had significant direct (β = −0.116), indirect (β = −0.096) and total (β = −0.212) effects on childhood OW/OB. Discussion There was a direct effect of feeding practices on childhood OW/OB; feeding practices indirectly predicted childhood OW/OB through temperament and eating behaviors in children aged 6–23 months. This study could help governments agencies, policymakers, and healthcare workers to establish optimal intervention programs targeting feeding practices through childhood eating behaviors and temperament to prevent childhood OW/OB.